Northern exposure. Seasons one and two [videorecording (DVD)]. - Morrow, Rob; Turner, Janine; Corbin, Barry; Cullum, John; Burrows, Darren E., 1966-; Corbett, John, 1961-; Geary, Cynthia; Miles, Elaine, 1960-; Phillips, Peg, 1918-2002 (Shout! Factory, 2020)
Return to one of television's quirkiest and most beloved towns! When New York doctor Joel Fleischman takes on a residency in Anchorage, he's sure that he's in for a cushy, comfortable gig. But upon his arrival in Alaska, Joel finds that he's a fish out of water when he's instead assigned to a tiny village where the eccentric townspeople first befuddle, then eventually charm, him.